Natural Control of Weed Invasions in Hyper-Arid Arable Farms: Allelopathic Potential Effect of Conocarpus erectus against Common Weeds and Vegetables - Anfal Alsharekh; Mohamed A. El-Sheikh; Abdulrahman A. Alatar; Eslam M. Abdel-Salam (Agronomy, 2022)
Utilization of plant allelopathic potential to control weed infestations provides an effective, cost-efficient, labor-free, and environmentally acceptable alternative to traditional chemical and mechanical methods. Conocarpus erectus, known as buttonwood, belongs to the Combretaceae family with high contents of phytochemicals and antioxidant activity. There have been no studies on the allelopathic potential of C. erectus. The present study (1) examined the allelopathic potential of C. erectus against selected weeds (Chenopodium murale and Amaranthus viridis) and crops (Solanum lycopersicum and Cucumis sativus) via investigating the growth inhibition ability of its aqueous extract, and (2) identified the potential allelochemicals found in this plant. Aqueous extracts were prepared from leaves, roots, and seeds of C. erectus by immersing the dried powder of the examined plant parts in sterile distilled water for 24 h on a shaker set to 180 rpm. The resulting filtrate was considered as 100% solution, and then dilutions were made to various concentrations (75%, 50%, and 25%). C. erectus leaves and seeds showed the highest rate of inhibition at all concentrations against Chenopodium murale and Amaranthus viridis grown in either Petri dishes or pots. Conversely, all the studied extracts did not show any toxic effects against tomato and cucumber plants grown in pots. In Petri dishes, a slight reduction in growth was observed. HPLC analysis of total phenolic contents in C. erectus methanolic extracts showed that leaves have the highest contents of gallic acid, caffeic acid, and ferulic acid (153.963, 69.135, and 39.801 ppm, respectively). The finding of the current study demonstrated that the part of the plant and the concentration of extraction have a significant effect on phytotoxicity. The positive results of this study might be used to develop environmentally-friendly herbicides for agricultural purposes.